Microstructure and mechanical properties of thixoforged complex box-type component of 2A12 aluminum alloy. (August 2020) - Jiang, Jufu; Zhang, Ying; Wang, Ying; Xiao, Guanfei; Liu, Yingze; Zeng, Li
Abstract: Complex box-type components of 2A12 aluminum alloy were thixoforged successfully, and their microstructures and mechanical properties were studied. Full filling status without surface defects was acquired by thixoforging a trapezoidal semisolid billet at the female die temperature of 420 °C and punch temperature of 340 °C. The maximum yield strength, ultimate tensile strength and elongation of the thixoforged component under optimized T4 treatment condition were 263.4 MPa, 414.2 MPa and 36.0%, respectively. Liquid segregation phenomenon happened at the upper edge of the component due to liquid flow and flow of liquid incorporating solid particles. Liquid fraction at the bottom part of the component was little, therefore severe plastic deformation mechanism of solid particles along with dynamic recrystallization was dominant. Dislocations, dislocation loops and dislocation bands of thixoforged 2A12 product were observed through transmission electron microscope (TEM). Deformation textures (Brass, Goss and S), recrystallization textures (Cube and R) and shear texture (rotated Cube) existed at the bottom region. Dispersoids Al20 Cu2 Mn3, Al7 Cu2 Fe particles and intermetallic phase S (Al2 CuMg) were speculated in the microstructure of thixoforged 2A12 component with T4 heat treatment. Dislocations strengthening, refinement strengthening and strengthening of the second phase codetermined the final mechanical properties. Graphical abstract: Unlabelled Image Highlights: Complex box-type components of 2A12 aluminum alloy were thixoforged directly, with maximum elongation 36.0%. Plastic deformation mechanism was dominant at the bottom part, along with dynamic recrystallization. Deformation textures (Brass, Goss and S), recrystallization textures (Cube and R) and shear texture (rotated Cube) existed. The second phases including Al20 Cu2 Mn3, Al7 Cu2 Fe and Al2 CuMg were speculated in the microstructure.